Cluster of cardiometabolic risk factors in children with GH deficiency: a prospective, case–control study. (16th January 2014) - Capalbo, Donatella; Mattace Raso, Giuseppina; Esposito, Andrea; Di Mase, Raffaella; Barbieri, Flavia; Meli, Rosaria; Bruzzese, Dario; Salerno, Mariacarolina
Summary Objective Growth hormone (GH) deficiency (GHD) in adults is associated with increased cardiovascular (CV) risk. Although some authors have documented the presence of early CV risk factors in untreated GHD children, results are still inconsistent. Aim of this study was to evaluate the effects of GHD and GH therapy on early cardiometabolic risk factors in a large cohort of children. Subjects and Methods Waist‐to‐height ratio (WHtR), triglycerides, total‐, low‐density lipoprotein (LDL), high‐density lipoprotein (HDL) cholesterol, atherogenic index (AI = total /HDL cholesterol), homocysteine, leptin, adiponectin, high‐sensitivity C‐reactive protein (hsCRP) and fibrinogen were evaluated in seventy‐one GHD children (9·8 ± 3·6 years) before and after 2 years of GH therapy. Seventy‐one healthy controls comparable with patients for age, sex and body mass index (BMI) were enrolled. Results Compared with controls, GHD children at study entry had higher WHtR (0·52 ± 0·05 vs 0·45 ± 0·19, P = 0·004), triglycerides (0·44 ± 0·98 vs −0·03 ± 0·73 SDS, P = 0·012), total cholesterol (0·28 ± 1·08 vs −0·46 ± 0·98 SDS, P < 0·001), LDL cholesterol (0·20 ± 0·90 vs −0·39 ± 1·06 SDS, P = 0·007), AI (3·19 ± 0·73 vs 2·77 ± 0·53, P = 0·001), homocysteine (8·45 ± 1·8 vs 7·72 ± 1·6 μm, P = 0·003), leptin (8·03 ± 4·2 vs 5·09 ± 1·9 ng/ml, P = 0·001) and fibrinogen (292·6 ± 33 vs 268 ± 31·4 mg/dl, P = 0·011). No differences were found in adiponectin or hsCRP. GH therapy was associated with a significant reduction in WHtR (P < 0·001), total cholesterol (P < 0·001), LDL cholesterol (P = 0·002), homocysteine (P = 0·044) leptin (P = 0·022) and fibrinogen (P = 0·001). Moreover, GH therapy was associated with a significant increase in adiponectin levels (P = 0·001). Conclusions Our data suggest that children with untreated GHD exhibit a cluster of early cardiovascular risk factors and that GH treatment exerts beneficial effects on these abnormalities.